Effect of Continuous Running on Selected Cardio Respiratory Endurance of College Men Students: Effects of Continuous Running on Cardiorespiratory Performances in College Men Students (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The present study was to ascertain the effect of continuous running on cardio-respiratory performances of college male students. To achieve this purpose of the study, thirty men students in the age group of 18 to 24 years were selected from the department of physical education, Annamalai University randomly. The selected subjects were categorized into two equal groups of fifteen each fifteen each for continuous running group and the control group. Group I underwent continuous running for three days per week for twelve weeks, whereas Group II acted as the control group who maintained their daily routine activities and no special training was given to them. Group I was subjected to cardio respiratory endurance which is the criterion variable of the present study. Necessary data for the present study was collected by administering cooper’s 12 minutes runwalk test both pre and post training period. The collected data were analyzed statistically through analysis of covariance (ANCOVA) to find out the significant differences, if any between the groups. The .05 level of confidence was fixed to test the level of significance, which was considered as an appropriate. The results of study stated there existed significant difference in the cardiorespiratory performances when the continuous running group and the control group were compared and analysed. It was also observed that there was significant improvement in cardio respiratory performances due to training in continuous running.